A PENINGKATAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN MENGGUNAKAN MODEL PPR PADA SISWA KELAS III SDN 127/II SUNGAI ARANG KECAMATAN BUNGO DANI - Abdul Zhafran (Jurnal Tunas Pendidikan, 2020)
The background of this research is the lack of awareness of students while studying Citizenship Education and the learning methods applied are less innovative and the value of Civics Education daily tests is still low. The objectives of this study were: 1) To determine the process of implementing the PPR model in improving the learning outcomes of Citizenship Education in class III SDN 127 / II Sungai Arang, Kecamatan Bungo Dani. 2) To determine the application of the Reflective Pedagogical Paradigm model in improving the learning outcomes of Citizenship Education in grade III SDN 127 / II Sungai Arang. This type of research is Classroom Action Research (PTK). The research setting consists of 1) research location 2) research time 3) research subjects. This research was conducted in two cycles. Cycle I had two meetings and cycle II had one meeting. The process of implementing the PPR model in improving the process and learning outcomes of Citizenship Education. The teaching process of teachers in the first cycle of meeting one with a value of 65% (Good enough) in the first cycle of meeting two with a total of 75% (Good), while the second cycle increased 80% (Very good). This process is also seen from the student learning outcomes. In the first cycle of meeting one, the value was obtained 60% (Enough) and in the first cycle the second meeting the value was obtained 65% (Enough). In the second cycle the value increased by 75% (Good). means that the teacher teaching process and student learning process has increased in cycle II.